Sandino's nation : Ernesto Cardenal and Sergio Ramírez writing Nicaragua, 1940-2012 - Henighan, Stephen, 1960- (McGill-Queen's University Press, 2014)
Ernesto Cardinal and Sergio Ramirez are two of the most influential Latin American intellectuals of the late twentieth and early twenty-first centuries. This book offers rigorous textual analyses of poems, memoirs, essays, and novels, interwoven with a sharply narrated history of Nicaragua.